PENYULUHAN PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SEKOLAH DASAR NEGERI HARJAMUKTI KELURAHAN SAWAH LUHUR KECAMATAN KASEMEN KOTA SERANG - Tiwi Rizkiyani; Rina Yulianti (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Children's health is one of the important aspects of child development that must be fulfilled and protected. In elementary school-age children, health problems will cause a decrease in learning ability which has an impact on reducing academic achievement. One of the health problems that occur in primary school-age children is related to personal and environmental hygiene problems due to low awareness of the importance of clean and healthy living behavior (PHBS). The implementation of PHBS in schools can reduce the risk of infectious diseases and infectious diseases in children. The implementation of PHBS in Harjamukti State Elementary School, Sawah Luhur Kelurahan, Kasemen, Serang City is carried out as one of the efforts to raise awareness of the importance of PHBS for students so that it aims to improve the ability to apply PHBS for themselves in a sustainable manner in daily activities, especially in the school environment. The counseling method used was lectures, interactive discussions, hand washing practice, and evaluation in the form of quizzes. The achievement of the activity was considered good by looking at the positive response of the students and the commitment to implement PHBS. Keywords: Counseling; Clean and Healthy Living Behavior; Elementary School.